2017
DOI: 10.1042/bsr20160621
|View full text |Cite
|
Sign up to set email alerts
|

Paired assessment of liver telomere lengths in hepatocellular cancer is a reliable predictor of disease persistence

Abstract: In the present study, we used a small series of highly defined patients, where we had matched timed peripheral blood samples (PBS), as well as paired liver biopsies obtained during collection of blood samples from patients with diagnosed hepatocellular carcinoma (HCC) and compared the correlation between the changes of telomere lengths in these defined samples. Patients included had either HCC alone or in conjunction with either pre-existing hepatitis B virus (HBV) or hepatitis C virus (HCV) infection. PCR-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Moreover, the change in the RTL of PBMCs could be extrapolated to the liver, as indicated by Feng et al [27]. In this work, they observed similar variations in RTL values of paired liver biopsy and PBMC samples from HCV-monoinfected and HBV/HCV-coinfected patients with hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the change in the RTL of PBMCs could be extrapolated to the liver, as indicated by Feng et al [27]. In this work, they observed similar variations in RTL values of paired liver biopsy and PBMC samples from HCV-monoinfected and HBV/HCV-coinfected patients with hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 80%
“…Telomerase RNA levels were found to be lower in the peripheral blood lymphocytes (PBLs) of HBV- and HCV-infected individuals that may contribute to immunosuppression [ 77 ]. Telomere length assessments in HCC patients infected with HBV or HCV demonstrated shorter telomere lengths not only in liver biopsied tissue, but also in PBLs [ 78 ]. Telomere attrition was not seen in HBV/HCV-noninfectious HCC.…”
Section: Telomere Dynamics and T-cell Exhaustion During Chronic/prmentioning
confidence: 99%
“…On the contrary, longer telomere length detected 10 years prior to diagnosis contributed to the risk of developing HCC ( 256 ). Finally, Feng et al ( 258 ) indicated that peripheral blood samples could be used to measure telomere length in HBV or HCV-infected patients, but not in non-infected ones. The viral genome may affect telomerase activity, thus affecting disease development and persistence ( 258 ).…”
Section: Digestive Systemmentioning
confidence: 99%